2020
DOI: 10.1021/acs.langmuir.0c00170
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Large Alumina Platelets and Silica Nanoparticles by Heteroaggregation and Sedimentation: Toward an Alternative Shaping of Nacre-Like Ceramic Composites

Abstract: Nacre-like ceramic composites are of importance in a wide range of applications, because of their mechanical properties, combining high mechanical strength and high fracture toughness. Those mechanical properties are the result of strongly aligned platelets glued in a matrix. Different methods exist to shape such 'brick-and-mortar' hierarchical structure. In this paper, it is proposed to use the phenomenon of heteroaggregation between silica nanoparticles and large alumina platelets. Experimental and numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It has been shown [16], that the heteroaggregation of silica nanoparticles and alumina platelets can help disaggregating the suspension. In this study, a third component is used, (Fig.…”
Section: Heteroaggregationmentioning
confidence: 99%
“…It has been shown [16], that the heteroaggregation of silica nanoparticles and alumina platelets can help disaggregating the suspension. In this study, a third component is used, (Fig.…”
Section: Heteroaggregationmentioning
confidence: 99%
“…Here, we show that such nacre-like ceramic composites can be obtained without addition of organic additives using simple shaping methods. Brownian dynamics simulations and experiments have indeed shown that using the heteroaggregation between the alumina platelets and the silica nanoparticles in aqueous suspensions yields at the same time a compact arrangement of the platelets and a good spatial distribution of the silica in between them [16].…”
Section: Introductionmentioning
confidence: 97%
“…An alternative, that avoids the introduction of organic compounds in the microstructure, is to take advantage of surface charges present at the surface of particles in aqueous suspensions. Previous studies have shown that the heteroaggregation of particles under the action of the electrostatic forces represents a promising method to control the arrangement of particles [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Another field of application is the stabilization of emulsions by heteroaggregates [20] [21], which could replace efficiently the use of traditional organic surfactants, which are not healthy nor environmental-friendly. Finally the use of binary components mixtures and heteroaggregation was employed for advanced ceramics [22], to obtain a well-designed porosity for example [23] [24], or for biomimetic materials [25]. In parallel, some studies have proposed some kinetic models to describe and predict the coagulation process [26] [27] [28] [29].…”
Section: Introductionmentioning
confidence: 99%
“…A very innovative granulation method in dilute suspension was proposed as a direct application, leading to well-designed dense and porous ceramic millimetric beads [38] [39] [40] [41]. Another recent application was a biomimetic assembly silica-alumina nacre-like composite [25]. In the literature, the addition of inorganic colloidal sols was reported for the stabilization of ceramic slurries.…”
Section: Introductionmentioning
confidence: 99%